Optimizing Cryptocurrency Portfolio Management through Innovative Tracker - Kumar Singh, Akhil; Balu, Shashi; Kaur, Arshdeep; Shivani Bansal; Aman (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cryptocurrency, or crypto, is a form of currency used for digitally secure transactions using cryptography. Cryptocurrency does not have any central regulatory authorities. It works on decentralized systems to record transactions and issue new units. Cryptocurrency is a digital payment system where transactions are verified and maintained by a decentralized system and do not need any authorization from the bank for digital entries. They are stored in digital wallets and a public ledger records the transactions Cryptocurrency is derived from the word encryption, the term used for verifying the transactions. The purpose of encryption is to provide a safe and secure way to transact payments or any other form of data. The transaction of the data takes place between the wallets and the public ledger. A Public ledger is a distributed system which is known as Blockchain, that is responsible for the records of the transactions and updating it. Computers generate cryptocurrency coins through complicated mathematical operations. The process in which these units of cryptocurrencies are called mining. The user of the coin just owns a key that allows the transaction of the records in the database. The most popular are bitcoin, ethereum, litecoin, ripple, namecoin, peercoin, etc.[3,4]